Federal management of the More Doctors Program: the role of the Ministry of Education - Erika Rodrigues de Almeida; Harineide Madeira Macedo; José Carlos da Silva (Interface: Comunicação, Saúde, Educação, 2019)
Abstract The More Doctors Program (PMM) has three axes of action and is grounded on the pedagogical guidelines of Permanent Education. Considering the Program’s scope, which ranges from the emergency supply of doctors to the expansion of the number of seats in undergraduate and medical residency courses, its management is interministerial, as the Ministry of Health and the Ministry of Education share responsibilities for its full operation. This article reports on the construction of the Ministry of Education’s experience of managing PMM, which includes the structuring of a new Directorate and new ways of doing management in this Ministry. It also points out the main difficulties and facilities throughout the process, and reflects on the perspectives and challenges for the Program’s continuity and sustainability.